Loss of dopaminergic neurons occurs in the ventral tegmental area and hypothalamus of rats following chronic stress: Possible pathogenetic loci for depression involved in Parkinson's disease. (October 2016) - Sugama, Shuei; Kakinuma, Yoshihiko
Highlights: Chronic RS reduce the number of TH-ir, mRNA expressing cells in the VTA. Chronic RS reduce the number of TH-ir, mRNA expressing cells in the AN. Neurons stained with cresyl violet are reduced in the VTA and AN following chronic RS. Abstract: Parkinson's disease (PD) is a neurodegenerative disease characterized by loss of dopaminergic (DA) neurons in the nigrostriatal and mesolimbic pathways including ventral tegmental area (VTA). Although several factors for the neuronal loss have been suggested, most of the PD cases are sporadic and idiopathic. In our previous study, we demonstrated the first evidence that solely chronic restraint stress (RS) induced the DA neuronal loss in the substantia nigra (SN). In this study, we further investigated whether chronic stress could affect other major DA systems, VTA and tuberoinfundibular system (TIDA), by using immunohistochemical and in situ hybridization techniques. The present study showed that, in the VTA, tyrosine hydroxylase (TH) immunoreactive neurons decreased by 9.8% at 2nd week, 19.2% at 4th week, 39.5% at 8th week, and 40.6% at 16th week during chronic RS as compared to control. Similarly, in the TIDA, the TH neurons decreased by 10.9% at 2nd week, 38.2% at 4th week, 56.3% at 8th week, and 57.1% at 16th week. The in situ hybridization results consistently demonstrated decreases in Th mRNA expressing cells in the VTA and TIDA in a comparable time dependent manner. Thus, exposure to chronic stress may simultaneously induce multiple neuronal loss of DA systems.